Butyrate-engineered yeast activates Nppa and Sgcg genes and reduces radiation-induced heart damage via the gut-heart axis - Jiahao Wu; Kaihua Ji; Guangbo Kang; Manman Zhang; Jigang Wang; Lina Wang; Mengxue Gao; Xiaoxiao Jia; Xinran Lu; Yan Wang; Xinran Gao; Yufei Guo; et al. (Pharmacological Research)
Radiotherapy is a method of treating cancer through radiation aimed at killing cancer cells or inhibiting their growth. However, radiotherapy has numerous side effects because it kills tumors while causing damage to normal cells or tissues. The literature shows that radiation can cause damage to heart tissue. This study found that engineered yeast that produced butyrate can maintain small intestinal barrier function by recovering GPR109A to reduce intestinal damage caused by abdominal irradiation in mice. We unexpectedly found that engineered yeast could mitigate irradiation-induced heart damage via the gut-heart axis. Mechanistically, engineered yeast enhanced taurine and nicotinamide metabolism by increasing the relative abundance of Akkermansia and Lachnospiraceae_NK4A136; then, yeast modulated cardiac function by activating the Sgcg and Nppa genes to attenuate cardiac damage induced by abdominal irradiation. Finally, we confirmed that engineered yeast mitigated cardiac damage caused by total body irradiation, which protected other vital organs through the intestinal tract. This study has a profound impact on cancer treatment, the emergence of engineered yeast will alleviate radiotherapy side effects and benefit patients.